The Influence of Nutrition Education with Booklet Media on the Knowledge of Nutrition in Athletes Pencak Silat in Pwnu Surabaya - Nidal Taftazani Albani Ijazi; Luthfi Rusyadi; Nuning Marina Pengge; Ergia Latifolia; Shivania Kathiresan (Politeknik Kesehatan Kemenkes Surabaya, 2024)
Pencak Silat athletes face challenges in nutritional knowledge which affects their performance. This study aims to assess the impact of nutrition education via booklets on their knowledge. This study employed experimental research using a one group pre- and post-testing. Data collection was conducted using a questionnaire and statistical tests using the Wilcoxon Test. The respondents used amounted to 36. The result showed that the Wilcoxon Test p-value (Asymp.Sig 2-Tailed) was 0.000 <0.05, Therefore, there was an impact on the knowledge of martial arts athletes at PWNU Surabaya on nutrition education through booklet media. The conclution is nutrition education using booklet media significantly affects the increase in knowledge of martial arts athletes at PWNU Surabaya.